# Solve Using the Square Root Property -x^2-10x+18=0 -x2-10x+18=0
Factor -1 out of -x2-10x+18.
Factor -1 out of -x2.
-(x2)-10x+18=0
Factor -1 out of -10x.
-(x2)-(10x)+18=0
Rewrite 18 as -1(-18).
-(x2)-(10x)-1⋅-18=0
Factor -1 out of -(x2)-(10x).
-(x2+10x)-1⋅-18=0
Factor -1 out of -(x2+10x)-1(-18).
-(x2+10x-18)=0
-(x2+10x-18)=0
Multiply each term in -(x2+10x-18)=0 by -1
Multiply each term in -(x2+10x-18)=0 by -1.
-(x2+10x-18)⋅-1=0⋅-1
Simplify -(x2+10x-18)⋅-1.
Apply the distributive property.
(-x2-(10x)–18)⋅-1=0⋅-1
Simplify.
Multiply 10 by -1.
(-x2-10x–18)⋅-1=0⋅-1
Multiply -1 by -18.
(-x2-10x+18)⋅-1=0⋅-1
(-x2-10x+18)⋅-1=0⋅-1
Apply the distributive property.
-x2⋅-1-10x⋅-1+18⋅-1=0⋅-1
Simplify.
Multiply -x2⋅-1.
Multiply -1 by -1.
1×2-10x⋅-1+18⋅-1=0⋅-1
Multiply x2 by 1.
x2-10x⋅-1+18⋅-1=0⋅-1
x2-10x⋅-1+18⋅-1=0⋅-1
Multiply -1 by -10.
x2+10x+18⋅-1=0⋅-1
Multiply 18 by -1.
x2+10x-18=0⋅-1
x2+10x-18=0⋅-1
x2+10x-18=0⋅-1
Multiply 0 by -1.
x2+10x-18=0
x2+10x-18=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=1, b=10, and c=-18 into the quadratic formula and solve for x.
-10±102-4⋅(1⋅-18)2⋅1
Simplify.
Simplify the numerator.
Raise 10 to the power of 2.
x=-10±100-4⋅(1⋅-18)2⋅1
Multiply -18 by 1.
x=-10±100-4⋅-182⋅1
Multiply -4 by -18.
x=-10±100+722⋅1
Add 100 and 72.
x=-10±1722⋅1
Rewrite 172 as 22⋅43.
Factor 4 out of 172.
x=-10±4(43)2⋅1
Rewrite 4 as 22.
x=-10±22⋅432⋅1
x=-10±22⋅432⋅1
Pull terms out from under the radical.
x=-10±2432⋅1
x=-10±2432⋅1
Multiply 2 by 1.
x=-10±2432
Simplify -10±2432.
x=-5±43
x=-5±43
Simplify the expression to solve for the + portion of the ±.
Simplify the numerator.
Raise 10 to the power of 2.
x=-10±100-4⋅(1⋅-18)2⋅1
Multiply -18 by 1.
x=-10±100-4⋅-182⋅1
Multiply -4 by -18.
x=-10±100+722⋅1
Add 100 and 72.
x=-10±1722⋅1
Rewrite 172 as 22⋅43.
Factor 4 out of 172.
x=-10±4(43)2⋅1
Rewrite 4 as 22.
x=-10±22⋅432⋅1
x=-10±22⋅432⋅1
Pull terms out from under the radical.
x=-10±2432⋅1
x=-10±2432⋅1
Multiply 2 by 1.
x=-10±2432
Simplify -10±2432.
x=-5±43
Change the ± to +.
x=-5+43
x=-5+43
Simplify the expression to solve for the – portion of the ±.
Simplify the numerator.
Raise 10 to the power of 2.
x=-10±100-4⋅(1⋅-18)2⋅1
Multiply -18 by 1.
x=-10±100-4⋅-182⋅1
Multiply -4 by -18.
x=-10±100+722⋅1
Add 100 and 72.
x=-10±1722⋅1
Rewrite 172 as 22⋅43.
Factor 4 out of 172.
x=-10±4(43)2⋅1
Rewrite 4 as 22.
x=-10±22⋅432⋅1
x=-10±22⋅432⋅1
Pull terms out from under the radical.
x=-10±2432⋅1
x=-10±2432⋅1
Multiply 2 by 1.
x=-10±2432
Simplify -10±2432.
x=-5±43
Change the ± to -.
x=-5-43
x=-5-43
The final answer is the combination of both solutions.
x=-5+43,-5-43
The result can be shown in multiple forms.
Exact Form:
x=-5+43,-5-43
Decimal Form:
x=1.55743852…,-11.55743852…
Solve Using the Square Root Property -x^2-10x+18=0   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top